An investigation of the reach of the interim Canada dental benefit for children under 12 years of age - Schroth, Robert J.; Youssef, Carol; Cruz de Jesus, Vivianne; Olatosi, Olubukola O.; Lee, Victor H. K.; Goubran, Saif; Khan, Eefa; Menon, Anil (Frontiers in Oral Health, 2025)
IntroductionThe Interim Canada Dental Benefit (CDB), introduced in 2022, provided financial assistance to families with children <12 years. This study analyzed data from the Canada Revenue Agency (CRA) during the program's entirety.MethodsData were accessed from the CRA for applicants and covered both the first (October 1, 2022–June 30, 2023) and second (July 1, 2023–June 30, 2024) periods. Rates of participation and 95% confidence intervals (CIs) were calculated using population data from Statistics Canada. Adjusted rates were calculated based on the proportion of children without private dental insurance, and without private or public insurance.ResultsOver the 21 months of the Interim CDB, 408,240 regular applications were made and 401M distributed to Canadian families. More applications were made during period 1 (P1) than period 2 (P2), but more funding distributed in P2; 197M for 204,270 applications in P1 and 203M for 203,970 applications in P2. Overall, 321,000 children received the Interim CDB in P1 and 328,040 in P2. Provinces with highest rates of child participation included Manitoba, Ontario, Nova Scotia, and Saskatchewan. The highest adjusted rates based on the proportion of children without private or public insurance were Nova Scotia (673.3/1,000, 95% CI: 658.5–688.4 P1 and 717.8/1,000, 95% CI: 702.5–733.3 P2), Northwest Territories (618.4/1,000, 95% CI: 560–681.3 P1 and 573.2/1,000, 95% CI: 517–633.8 P2), and Saskatchewan (495.1/1,000 P1, 95% CI: 486.5–503.7 and 528.3/1,000, 95% CI: 519.5–537.2 P2)ConclusionsRegions with access to care challenges had higher rates uptake of the Interim CDB when adjusting for the lack of private or public insurance. Findings from this study may help inform policy decisions and reach of the CDCP.